Broadband Applications of a Tunable Nano-Rod Metaferrite. (March 2021) - Rybin, Oleg; Shulga, Sergey
Abstract: The rigorous analytical model of broadband effective electromagnetic response of the two-component metaferrite is presented in this study in the range up to THz frequencies. The metaferrite is a square array of ferric or ferromagnetic infinitely long cylinders of circular cross section symmetrically imbedded into homogenous isotropic dielectric host medium. It is assumed that the cylinders are fully or partially magnetized by a dc biasing magnetic field directed along the cylinder axes. Expressions of the complex effective permeability and permittivity tensors are obtained in the study. Expressions of the complex effective relative permeability and permittivity transverse to the direction of magnetization are derived and analyzed as functions of the frequency of incident electromagnetic wave and constitutive parameters of the metaferrite. It is shown that tuning a dc biasing magnetic field enables to effectively change the transmittivity and reflectivity of the metaferrites in the considered frequency range. We were also able to show that a layer of the metaferrite can be used for exciting surface plasmons at GHz frequencies. Finally, we have discussed the principal possibility of usage of the considered metaferrite for fabricating the substrates of miniaturized patch antennas with improved performance.